Belief reinforcement: One reason why costs for low back pain have not decreased - Zusman, Max (Dove Medical Press Ltd, 2013)
Recent figures show that there has been no change in the upward trend of direct and indirect costs for the largely benign symptom of low back pain in Western societies. This is despite greater understanding and the recommendation of a much more conservative and independent approach to its management. Moreover, in recent years, several large-scale education programs that aim to bring knowledge of the public (including general practitioners) more in line with evidence-based best practice were carried out in different countries. The hope was that the information imparted would change beliefs, ie, dysfunctional patient behavior and biomedical practice on the part of clinicians. However, these programs had no influence on behavior or costs in three out of the four countries in which they were implemented. It is argued that one reason for the overall lack of success is that it is extremely difficult to alter the potentially disabling belief among the lay public that low back pain has a structural mechanical cause. An important reason for this is that this belief continues to be regularly reinforced by the conditions of care of a range of “hands-on” providers, for whom idiosyncratic variations of that view are fundamental to their professional existence.